Multivariate statistical analyses for Fe-Ti-V oxide ore deposit in Wajilitag area of Tarim Basin and its application for metallogenic prediction - Zhao, Yali; Liu, Haoying; Li, Zilong; Zou, Siyuan; Sun, Haowei; Li, Yinqi; Yang, Shufeng; Chen, Hanlin; Cheng, Jun (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2016)
The giant Wajilitag Fe-Ti-V oxide ore deposit outcropping in the Bachu area of Tarim Basin, is closely linked with the formations of the Early Permian Tarim Large Igneous Province. The correlations of major elements and metal elements(Fe, Ti and V) of the rock and ore samples from both outcrops and drill holes were studied by multivariate statistical analyses. The relationship between Fe-Ti and major elements was studied by the method of correlation analysis and regression analysis using the SPSS software. Correlation analysis of the drill hole data shows that Fe, Ti and V contents have positive correlations with each other. The equation of V=-4.984+0.360 Fe+0.984Ti among Fe, Ti and V elements is also established to predict vanadium content when Fe and Ti contents are known. The Fe-Ti-V three-dimensional cubic charts are drawn to establish the spatial distribution mode and predict the potential ore body using the visualization of Matlab. Our study shows that the contents of Fe sub(2) O sub(3T),TiO sub(2) and